Effects of surgical intervention on disease activity of rheumatoid arthritis: Cases of surgery for rheumatoid arthritis of the lower limbs treated with biologics. Issue 4 (July 2014) - Oh, Koei; Ishikawa, Hajime; Abe, Asami; Otani, Hiroshi; Nakazono, Kiyoshi; Murasawa, Akira
Abstract Objectives. In order to verify combination therapy with drugs and surgery for rheumatoid arthritis (RA), we evaluated changes in clinical outcome affected by surgical intervention in the patient treated with biologics and investigated the effects of surgery on disease activity. Methods. Fifty-five lower limb joint surgeries were performed in 48 patients under biological therapy. DAS28-ESR, modified Health Assessment Questionnaire (mHAQ) score, PtGA and serum CRP were examined just before surgery, at 6 months and at 12 months after surgery. A kind of suitable medication and its dose were investigated. Results. Preoperative DAS28-ESR significantly decreased from 3.71 ± 1.19 (mean ± SD) to 3.37 ± 1.22 at 6 months and to 3.24 ± 1.05 at 12 months postoperatively. mHAQ score did not change, but, PtGA and serum CRP improved. In 43 (78.2%) patients in whom no change or decrease in medication during the follow-up period, excluding the effect of drugs, DAS28-ESR also decreased significantly from 3.53 ± 1.17 to 3.16 ± 1.16 at 6 months, and to 3.16 ± 0.98 at 12 months. Conclusions. Lower limb surgery performed under biological therapy enhances the effects of not only improving joint function but also of ameliorating systemic disease activity.